Sustainable Branding: How Green Marketing Influences Consumer Purchase Intentions - Adinugroho, Iwan; Mohamad Sajili, Nurul Giswi Karomah , (YUME : Journal of Management, 2025)
This study presents a systematic literature review (SLR) aimed at synthesizing the current body of knowledge on how green marketing strategies influence consumer purchase intentions within the framework of sustainable branding. Based on an in-depth analysis of 52 peer-reviewed articles published between 2013 and 2023, the review identifies five core green marketing dimensions—eco-labeling, green advertising, sustainable product innovation, environmental brand image, and corporate environmental practices—as key drivers of consumer behavior. These strategies exert their influence through several mediating and moderating psychological constructs, including green trust, perceived value, environmental concern, brand credibility, and emotional engagement. The findings further reveal contextual variations across cultures, industries, and geographical settings that shape the effectiveness of green marketing interventions. While the theoretical foundations are supported by established models such as the Theory of Planned Behavior and signaling theory, the literature still lacks methodological diversity, particularly in terms of longitudinal and experimental research. This study contributes to theory development by offering an integrated conceptual framework and provides practical insights for marketers seeking to align sustainability initiatives with consumer values to enhance brand loyalty and environmentally responsible purchasing behavior. Keywords: Green Marketing; Sustainable Branding; Consumer Purchase Intention; Environmental Concern; Green Trust